PEMILIHAN METODE AKUNTANSI PERSEDIAAN DAN PENGARUHNYA PADA EARNING PRICE RATIO (STUDI EMPIRIS PERUSAHAAN YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEX (JII) TAHUN 2016-2018) - Muhammad Junaidi; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTEarning Price Ratio (PER) is a ratio related to earnings per share and the price is assessed by the coefficient of variation and earnings per share value on the price of common shares. PER is used by various parties or investors to determine or choose which stocks are suitable for investment. Therefore, this research seeks to learn about the selection of inventory accounting methods that can affect the income price ratio. This study analyzes companies listed in the Jakarta Islamic Index (JII) 2016-2018. The variables in this study are FIFO and AVERAGE. The sample in this study were 18 companies. Based on the test results, it shows that the simultaneous accounting method (FIFO and AVERAGE) affects the income price ratio. Partial testing shows that the FIFO variable has no significant effect on the Earning Price Ratio and the AVARAGE variable has a significant effect on the Earning Price Ratio.Keywords: FIFO, AVERAGE, and Earning Price Ratio